Description of two new Panamanian species of Acanthocinini and notes on Eleothinus abstrusus Bates (Coleoptera, Cerambycidae, Lamiinae) - Heffern, Daniel; Santos-Silva, Antonio (Zootaxa, 2022)
Two new species of Acanthocinini are described from Panama: Hyperplatys rileyi and Leptostylus panamensis. Notes on chromatic variation and the invalid lectotype designation for Eleothinus abstrusus Bates, 1881 are provided.